QUINTANILLA, Pablo; César ESCAJADILLO y Richard Antonio OROZCO. Pensamiento y acción. La filosofía peruana a comienzos del siglo XX. Lima: Instituto Riva- Agüero, PUCP, 2009. - Sotomarino, Roxana (2009)
No contiene resumen